(untitled) (Journal of the College of Basic Education, 2025)
This research aims to ascertain how the Scamper skills including tennis serve learning. To determine the importance of the variations in the experimental and control research groups’ post-test outcomes of specific cognitive and learning the sending skill for students. The research community consisted of second year students in The Department of Physical Education and Sports Sciences of Al-Mustansiriya University’s College of Basic Education, for the 2024–2025 school year. There are 120 pupils total, divided among six courses, including (1-2-3-4), and by random method, Class (3) was chosen as the control group, and Class (1) as the experimental group. The sample proportion from the original community was equal to (26.09), and the researcher used a sample of thirty kids for the field experiment, with fifteen students in each group. One of the researcher’s most significant findings is that the SCAMPER technique and the teacher’s learning the skill of serving for students. skills and learning how to serve pupils, the experimental group has an advantage over the control group. One of the most crucial suggestions is for educators to employ the SCAMPER technique while teaching certain cognitive and acquiring abilities The ability of students to serve in tennis.